2022
DOI: 10.1186/s13059-022-02750-7
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis APOLO and human UPAT sequence-unrelated long noncoding RNAs can modulate DNA and histone methylation machineries in plants

Abstract: Background RNA-DNA hybrid (R-loop)-associated long noncoding RNAs (lncRNAs), including the Arabidopsis lncRNA AUXIN-REGULATED PROMOTER LOOP (APOLO), are emerging as important regulators of three-dimensional chromatin conformation and gene transcriptional activity. Results Here, we show that in addition to the PRC1-component LIKE HETEROCHROMATIN PROTEIN 1 (LHP1), APOLO interacts with the methylcytosine-binding protein VARIANT IN METHYLATION 1 (VIM1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 132 publications
1
32
0
Order By: Relevance
“…Beyond those mentioned above, APOLO is also shown to coordinate VARIANT IN METHYLATION 1 (VIM1) to form APOLO -LHP1-VIM1 complex, directly regulating the transcription of the auxin biosynthesis gene YUCCA2 . Interestingly, compared to APOLO , the sequence of lncRNA UHRF1 in humans showed poor similarity but displayed similar performance in transcription regulation of YUCCA2 [51] , predicting that analysis of conservative regulatory mechanisms may be a feasible approach to study the conservation of lncRNAs. The coordination regulation to target loci between lncRNAs and histone modifiers reflects the ability of lncRNAs to affect gene regulation through recruiting, decoy mechanisms, and interaction with histone modifiers.…”
Section: Survey Of Functional Lncrnas Associated With Epigenetic Modi...mentioning
confidence: 99%
“…Beyond those mentioned above, APOLO is also shown to coordinate VARIANT IN METHYLATION 1 (VIM1) to form APOLO -LHP1-VIM1 complex, directly regulating the transcription of the auxin biosynthesis gene YUCCA2 . Interestingly, compared to APOLO , the sequence of lncRNA UHRF1 in humans showed poor similarity but displayed similar performance in transcription regulation of YUCCA2 [51] , predicting that analysis of conservative regulatory mechanisms may be a feasible approach to study the conservation of lncRNAs. The coordination regulation to target loci between lncRNAs and histone modifiers reflects the ability of lncRNAs to affect gene regulation through recruiting, decoy mechanisms, and interaction with histone modifiers.…”
Section: Survey Of Functional Lncrnas Associated With Epigenetic Modi...mentioning
confidence: 99%
“…The dynamic formation of the chromatin loop between APOLO and PID is negatively correlated with APOLO expression levels. For APOLO ‐mediated activation of distant gene expression, it acts as a decoy for LHP1 and/or VARIANT IN METHYLATION 1 (VIM1) by forming R‐loops via base pairing with the DNA of target genes (Fonouni‐Farde et al, 2022). Similarly, the lncRNA MARNERAL SILENCING ( MARS ), which originates from the Arabidopsis marneral cluster, decoys LHP1 to limit H3K27me3 levels and facilitates an abscisic acid (ABA)‐responsive enhancer, including chromatin loop formation around adjacent genes (i.e., MARNERAL SYNTHASE 1 ( MRN1 ), CYP705A12 and CYP71A16 ), thus promoting their transcription in response to ABA (Roule et al, 2022).…”
Section: Regulatory Lncrnas In Plantsmentioning
confidence: 99%
“…119,120 APOLO functional characterization was also extended to show that in the case of the auxin biosynthesis gene YUCCA2, it can interact with the DNA methylation regulator VARIANT IN METHYLATION 1 (VIM1) in addition to LHP1 and modulate both DNA methylation and H3K27me3 deposition at the YUCCA2 promoter. 121 Another important example of a lncRNA mediating a repressive chromatin loop was discovered by, 30 who characterized COLDWRAP as being transcribed in the sense direction 225 base pairs upstream of FLC using RT-qPCR and interacting with CLF using RIP-RT-PCR during vernalization. RNA binding assays demonstrated its interaction with CLF occurred at the 5 0 end and was dependent on its secondary structure, and decreased H3K27me3 accumulation over FLC in COLDWRAP RNAi lines suggested this interaction was necessary for proper CLF activity.…”
Section: Mediating Chromosomal Looping Dynamicsmentioning
confidence: 99%
“…Additional studies confirmed that two such genes had similar APOLO target dynamics (this time in cold‐treated plants): ROOT HAIR DEFECTIVE 6 ( RHD6 ) and EXTENSIN 3 ( EXT3 ), though now it involves an interaction with the transcription factor WRKY42, suggesting these two may be working together alongside the target transcription factor RHD6 to regulate many root hair elongation processes 119,120 . APOLO functional characterization was also extended to show that in the case of the auxin biosynthesis gene YUCCA2 , it can interact with the DNA methylation regulator VARIANT IN METHYLATION 1 (VIM1) in addition to LHP1 and modulate both DNA methylation and H3K27me3 deposition at the YUCCA2 promoter 121 …”
Section: Mediating Chromosomal Looping Dynamicsmentioning
confidence: 99%